Comparative Analysis of Accounting Information’s Quality Pre and Post IFRS Adoption - Mira Apriliana Sari; Liza Alvia; Agrianti Komalasari; Sari Indah Oktanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Adoption of IFRS in Indonesia began in 2008, namely the initial adoption stage of IFRS based on Indonesia's commitment to support its achievements in one global accounting standard at the G20. IAI itself formulated the full adoption of IFRS in several stages, namely (1) the initial stage of IFRS adoption which began in 2008, (2) the convergence stage of preparation for full adoption of IFRS in 2010, (3) the first stage of full adoption of IFRS which began in 2012, (4) the second stage of full adoption of IFRS in 2015, (5) the third stage of full adoption of IFRS in 2018, (6) and the fourth stage of full adoption of IFRS in 2020. IFRS adoption is sought as a form of improving good financial reporting in improving quality of accounting information. This research will examine differences in the quality of accounting information before and after full adoption of IFRS. This research will take a sample of telecommunications sub sector companies,healthcare, and consumer non-cyclical registered as a member of the BEI. This research examines the value relevance of Ohlson's stock price proxy. The analysis technique used is paired sample t-test with a significance level of 5%. This research concludes that the full adoption of IFRS stage one has contributed to improving the quality of accounting information. This research shows that the quality of accounting information as seen from its value relevance will increase followed by a high increase in disclosure.